A Strengths-based approach to coaching mental touchness - Gordon, S.; Gucciardi, Daniel (Routledge, 2011)
Developing mental toughness has become a major focus for athletes, coaches, sport teams and organizations. Emerging research has supported a variety of influences (e.g., coaches, parents, self)and mechanisms (e.g., reflecting on our experiences, coach motivational climate) by which mental toughness development likely occurs. In this article we focus on a strengths-based approach to mental toughness development, which has received scant attention within the sport psychology literature. A brief history of strengths approaches to the development of human potential is presented and contrasted with assumptions of traditional psychological skills training. We then describe how a strengths-based approach was translated into practice using an example from professional cricket.The guidelines have been shown to be effective in elite sport settings, but we believe they may also prove effective in youth sport settings.